WITNESSES TESTIMONY WHO HAVE NO COMPETENCE IN THE CORRUPTION CRIME - Fikri Nawawi (UNISSULA, 2018)
Calculation of state losses can only be done by a witnesses. Witnesses here are not only witnesses in the field of financial audit but also engineers who will calculate the feasibility of construction of a building in case of corruption was related to the construction field. Witnesses who has the competence docalculating the quantity of a building and the price of a building is a person who has a construction management certification. Description of the Construction Witnesses who have no competence in the matter of corruption, the statement becomes invalid.